Salvinia natans: A potential test species for ecotoxicity testing. (December 2020) - Cui, Rongxue; Nam, Sun-Hwa; An, Youn-Joo
Abstract: Although macrophytes are known to play vital roles in aquatic ecosystems, most quantitative aquatic toxicity data focus on fishes, water fleas, or algae, with limited ecotoxicity data published on macrophytes. Salvinia natans is a fast-growing plant commonly found in freshwater habitats. In this study, we verified a suitable disinfectant for preventing foreign contamination and formulated a culture medium for ensuring high productivity of S. natans . Finally, we established methodology for S. natans to be used in ecotoxicity testing of heavy metals and pesticides. As global regulations are being developed to harmonize guidelines and laboratory test species, S. natans is emerging as a potential candidate. The toxicity data publicly available for S. natans are very limited; hence, this study reports an advantageous culturing technique to optimize healthy growth of this species in the laboratory and presents optimal toxicity results, achieved by modifying the currently available test guidelines for Lemna . Our findings expand the currently limited range of test species for aquatic toxicity assays. We conclude that S. natans could serve as a valuable test species for aquatic toxicity assays. Graphical abstract: Image 1 Highlights: Salvinia natans is an advantages ecotoxicity test species. Toxicity testing of heavy metals and a pesticide were performed with S. natans. Optimal disinfecting conditions and culture medium for S. natans were determined. Optimal disinfecting condition for S. natans was 1% citric acid for 1 min. The Steinberg medium was the most suitable for promoting growth. Abstract : This study proposes S. natans as an important addition to the currently limited taxonomic spectrum of species used for aquatic toxicity assays.